FINANCIAL RATIO ANALYSIS TO ASSESS THE FINANCIAL PERFORMANCE OF PT. ANGKASA PURA I (PERSERO) - Koapaha, Hartini Pop; Supit, Verlyanna Excellentsia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Assessing the financial performance of a company is important because it can show and measure the extent to which a company’s financial condition is through financial statement analysis. Financial statement analysis can be done using several analytical techniques, one of which is financial ratio analysis. This study aims to assess the financial performance of PT. Angkasa Pura I (Persero) using financial ratio analysis. The research method used is descriptive comparative with a quantitative approach. This study utilizes secondary data sources, namely, financial reports for 2018, 2019 and 2020 obtained from the official website of PT. Angkasa Pura I (Persero). The data were analyzed using financial ratio analysis and compared with previous years. The financial ratios used are liquidity ratios, solvency ratios, profitability ratios and activity ratios. The results of the study using the liquidity ratio measured using the current ratio and quick (acid-test) ratio indicate that there is poor liquidity performance from year to year. The solvency ratio as measured by the debt to equity and debt to asset ratios shows that the solvency performance is not good and is increasing every year. Profitability ratios measured using net profit margin, return on equity, return on assets and operating profit margins show that profitability performance is not good and is decreasing every year. The activity ratio shows that activity performance is decreasing as seen from total asset turnover and fixed asset turnover. The four groups of ratios show a declining financial performance from year to year. However, the four ratio groups in 2020 experienced a sharp decline due to COVID-19. Â Keywords: Financial performance, liquidity ratios, solvability ratios, profitability ratios, activity ratios.